Dampak Besaran Muzaraah di Desa Glinggang Terhadap Tingkat Kesejahteraan Petani Penggarap - Muhklison, Aldo; Rachmawati, Lucky (Universitas Negeri Surabaya, 2021)
This study aims to describe the implementation and impact of muzara'ah on the welfare of farmers and rice field owners in Glinggang village. The research method used in this study is a qualitative method. Data sources used in the form of informants, namely small farmers and rice land owners in Glinggang Village. There are two data in this study, primary data and secondary data. Data in the form of sentence expressions spoken by informants. Collecting data in this study by observation, interviews, and record techniques Data analysis method used in this study is a qualitative analysis method in the form of inductive reasoning. Data verification uses technical triangulation. This research produces (a) management of human data sources and (b) the impact of muzara'ah for the welfare of farmers and rice field owners in Glinggang Village, Sampung District, Ponorogo Regency.